Cold-water immersion alleviates intestinal damage induced by exertional heat stroke via modulation of gut microbiota in rats - Xuan, Lyu; Sun, Xiaojun; Wang, Baozhong; Chen, Feng; Yi, Yuhao; Mao, Handing; Wang, Yuxi; Zhao, Guifeng; Wang, Jiaxing; Zhang, Yuxiang (Frontiers in Microbiomes, 2025)
ObjectiveThe pathogenesis of exertional heatstroke (EHS) involves substantial contributions from gut microbiota and their metabolites. In this study, we assessed whether cold water immersion (CWI) mitigates EHS-induced intestinal damage via alterations in the microbiome.MethodsAn EHS model was created with 18 Wistar rats divided into three groups, that is, the EHS group comprising rats with exertional heat stroke, the CWI group with rats with heatstroke treated with cold water immersion, and the control (CTRL) group (rats with normothermia control). Pathological changes, core temperature (Tcore), and lactic acid (Lac) and endotoxin lipopolysaccharide (LPS) levels were evaluated. Fecal samples were subjected to metagenomic shotgun sequencing and liquid chromatography–mass spectrometry for microbiota and metabolomic profiling.ResultsHematoxylin and eosin staining showed that CWI treatment significantly reduced EHS-induced intestinal congestion, edema, and necrosis compared to the EHS group. The EHS group had the highest Tcore, while the CWI group had significantly lower Tcore than the EHS group. The CWI group had significantly reduced LPS and Lac levels, similar to those observed in the CTRL group. Microbiome analysis indicated that EHS disrupted gut bacteria, with an increase in the proportion of pathogens such as Desulfovibrio fairfieldensis, Desulfamplus magnetovallimortis, and Desulfococcus oleovorans (P<0.05). CWI treatment resolved these disturbances and restored the gut microbiota to a level similar to that of the CTRL group. Metagenomic analysis showed that CWI restored gut microbiota diversity (Shannon index, P<0.05), significantly reducing the proportion of pathogenic Desulfovibrio. Metabolomic profiling identified key metabolites, such as inosine, hypoxanthine, guanosine, and taurine (Variable importance in projection>1, P<0.05 with P-values adjusted for multiple comparisons using the Benjamini-Hochberg method, FDR<0.05), differentiating between the CWI and EHS groups.ConclusionThe metabolites inosine, taurine, hypoxanthine, and guanosine correlated with restored gut microbiota, reduced proportion of Desulfovibrio, and attenuated inflammation (lower LPS/Lac), suggesting that their dual role in mitigating intestinal damage. These findings underscore the therapeutic potential of CWI by modulating microbial-derived metabolites, highlighting its impact on the intestinal health of patients with EHS.